The Zionist ideas : visions for the Jewish homeland--then, now, tomorrow - Troy, Gil; Sharansky, Natan, 1948- (Lincoln : University of Nebraska Press, 2018)
"The most comprehensive Zionist collection ever published, The Zionist Ideas: Visions for the Jewish Homeland --Then, Now, Tomorrow builds on Arthur Hertzberg's classic The Zionist Idea, showcasing more than 170 visionaries and shedding light on the surprisingly diverse and shared visions for realizing Israel as a democratic Jewish state"--
Introduction: How Zionism’s Six Traditional Schools of Thought Shape Today’s Conversation -- Part One. Pioneers: Founding the Jewish State. -- 1. Pioneers: Political Zionism -- 2. Pioneers: Labor Zionism -- 3. Pioneers: Revisionist Zionism -- 4. Pioneers: Religious Zionism -- 5. Pioneers: Cultural Zionism -- 6. Pioneers: Diaspora Zionism -- Part Two. Builders: Actualizing and Modernizing the Zionist Blueprints. -- 7. Builders: Political Zionism -- 8. Builders: Labor Zionism -- 9. Builders: Revisionist Zionism -- 10. Builders: Religious Zionism -- 11. Builders: Cultural Zionism -- 12. Builders: Diaspora Zionism -- Part Three. Torchbearers: Reassessing, Redirecting, Reinvigorating. -- 13. Torchbearers: Political Zionism -- 14. Torchbearers: Labor Zionism -- 15. Torchbearers: Revisionist Zionism -- 16. Torchbearers: Religious Zionism -- 17. Torchbearers: Cultural Zionism -- 18. Torchbearers: Diaspora Zionism.
Includes bibliographical references.
"Published by the University of Nebraska Press as a Jewish Publication Society book."
Online resource; title from PDF title page (EBSCO, viewed March 6, 2018).
eBooks on EBSCOhost
Keywords: Zionism -- History -- Sources; RELIGION -- Judaism -- History; SOCIAL SCIENCE -- Jewish Studies; HISTORY -- Middle East -- Israel; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Zionism; History; Sources